Whitewashing criminology: a critical tour of Cesare Lombroso’s Museum of Criminal Anthropology - Arford, Tammi (Critical criminology, 2022)
In this article, we guide readers through a narrative tour of the Cesare Lombroso Museum of Criminal Anthropology (Museo di Antropologia Criminale Cesare Lombroso) in Turin, Italy. We describe and analyze the museum’s displays, pointing to the rhetorical devices and narrative strategies employed to "whitewash" Lombroso’s historical legacy and the destructive pseudoscientific endeavor of criminal anthropology. The museum is imbued with an apologist narrative that reinforces the myth of Western progress as humanity’s consummate achievement and largely dismisses Lombroso’s white supremacy and misogyny as "flaws" in his work rather than symptomatic of dominant ideology. We argue that, by eliding discussions of the sexism, racism, and colonial logic inherent to Lombroso’s work, as well as the countless social harms that have resulted from his legacy, the museum, itself, perpetuates social harm.